Radiocarbon dating of the Bakhshālī manuscript - Chivall, D; Lladó-Buisán, V; Howell, D; Evison, G (University of Oxford, 2024)
This report presents radiocarbon determinations on Bakhshālī Folios 15, 16, 23, 33, and 55.